Title: Hegel’s Philosophy of Politics - Prak, Samphose; Leeka, Jaras; Keo, Ratanak (Journal of Graduate MCU KhonKaen Campus, 2022)
This book review aims to present Hegel’s philosophy of politics to reflect on idealism, identity, and modernity. What did Hegel want? The book review will find two rule-based approaches:.1) pushing the state–run by morality and 2) letting people live free without a coercive manner from the state. The two- approaches, on the other hand, will find in this book because it is a mechanism for providing a better state. In addition, the fundamental theory of Hegel is political thought that focuses on free will (freedom), reason, and clear comprehension. In this regard, those theories are interdependent components of the metaphysics or applied philosophy of political thought in reality.